Transition from Pediatric to Adult HIV Care for Young Women Living with HIV. (23rd March 2020) - Kennedy, Victoria Logan; Mellor, Kaitlyn Luisa; Brophy, Jason; Bitnun, Ari; Alimenti, Ariane; Kakkar, Fatima; Logie, Carmen Helen; Webster, Kath; Proulx-Boucher, Karène; Ding, Erin; Jabbari, Shahab; Kaida, Angela; et al.
Transitioning from pediatric to adult care is a complicated process for youth with chronic illnesses. This study elucidates the unique factors affecting transition preparedness and perception of adult HIV care among a cohort of young women with HIV. Between 2013 and 2015, 48 women with HIV, who had experience with pediatric HIV care, were enrolled in a large Canadian cohort study. Variables were self-reported during peer-administered surveys. Only 60% reported feeling prepared for transition. Having never had contact with child protection services ( P = .049), never been in foster care ( P = .011), never been in a group home ( P = .036), reporting a higher current CD4 count ( P = .033), and reporting a younger ideal age for transition ( P = .041) were associated with transition preparedness. Eighty-four percent reported equivalent or better HIV care following transition. Correlates of equivalent/better care following transition included lower personal income ( P = .023), higher CD4 count ( P = .021), care by an adult infectious diseases specialist ( P = .002), and transition preparedness ( P = .005). Our findings highlight the importance of adequate transition preparation and its effect on perception of care following transition.